A Massive White Dwarf or Low-mass Neutron Star Discovered by LAMOST - Zhao, Xinlin; Wang, Song; Wang, Pengfei; Zheng, Chuanjie; Yuan, Haibo; Liu, Jifeng (The Astrophysical journal, 2024)
We report the discovery of a close binary J0606+2132 (Gaia DR3 3423365496448406272) with P obs = 2.77 days containing a possible massive white dwarf (WD) or a neutron star (NS) using LAMOST spectroscopic data. By a joint fitting of the radial velocity from LAMOST and the light curve from TESS, we derived a circular Keplerian orbit with an inclination of i = 81.°31 − 7.85 ° + 6.26 ° , which is consistent with that derived from v sin i . Together with the mass of the visible star, we derived the mass of the invisible object to be 1.34 − 0.40 + 0.35 M ⊙ . Spectral disentangling with the LAMOST medium-resolution spectra shows no absorption feature from an additional component, suggesting the presence of a compact object. No X-ray or radio pulsed signal is detected from ROSAT and FAST archive observations. J0606+2132 could evolve into either a Type Ia supernova or an NS through accretion-induced collapse if it is a WD or into an intermediate-mass X-ray binary if it is an NS.